Exploring Misconceptions of Light and Shadow Formation among Senior High School Students: A Qualitative Study in Physics Education - Nurlailah; Utama, Rodika; Mustava, Oki; Toifur, Moh.; Dina, Devi Farah (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study explores senior high school students’ misconceptions of light and shadow formation within the context of physics education. Despite being a fundamental concept in optics, many students continue to experience difficulties in understanding the principles of light propagation, the rectilinear nature of light, and the conditions required for shadow formation. This research employed a qualitative exploratory design involving 32 students from Grade X and XI science classes in Central Java, Indonesia. Data were collected through diagnostic tests and semi-structured interviews, which allowed in-depth identification of alternative conceptions. The analysis revealed three dominant categories of misconceptions: (1) perceiving light as a substance that “flows” from the source, (2) assuming that shadows are independent objects rather than regions of blocked light, and (3) misunderstanding the relationship between light intensity, distance, and shadow clarity. These findings confirm that students often rely on intuitive reasoning based on everyday experiences rather than scientific explanations. The discussion highlights the implications for physics instruction, particularly the need for teaching strategies that incorporate conceptual change models and inquiry-based learning to address students’ alternative frameworks. The study concludes that addressing misconceptions in optics requires not only emphasizing correct scientific principles but also engaging students in reflective and interactive learning processes that directly confront their prior conceptions.